Leadership in Action Inklings - Twenty-Five Years - Seemingly Quick as a Heartbeat - Campbell, David P. (Center for Creative Leadership, 1999)
David Campbell reflect on being at CCL for twenty-five years.
Title from content provider
Keywords: Leadership